2022
DOI: 10.3390/ijerph192114141
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Small-Sided Games and Behavioral Interventions on the Physical and Motivational Outcomes of Youth Soccer Players

Abstract: The objective of this study was to test the effects of two types of intervention, one based on small-sided games (SSGs), and the other one that had, in addition, a behavioral component consisting of goal setting, public posting, and positive reinforcement. The participants were 16 male soccer players aged 12–14 years old who participated in a couple of training sessions per week between August and November 2021. We used Playr Catapult GPS devices to assess the effect of the intervention on the total distance c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…It makes sense for HIIT to include SSGs since the players would also improve technical and tactical elements and their decision-making processes, which are required for playing soccer ( Davids et al, 2013 ; Trecroci et al, 2020 ) Therefore, the next aim was to determine if participants would exceed the ANT and achieve PFT intensity during four-versus-four matches on a 25 m × 35 m pitch that reflect the game conditions required in the specific HIIT proposed. The parameter frequently used in coaching practice to determine the effort intensity during the game is HR ( Brandes et al, 2012 ; Aşçı, 2016 ; Konefał et al, 2023 ), which can be measured with precision and accuracy using available measurement technologies ( Beenham et al, 2017 ; Gómez-Carmona et al, 2020 ; Pop et al, 2022 ). In this study, soccer players achieved HR max values that exceeded the intensity found at the ANT five-fold during six 3-min matches, even though they did not reach such intensity at the PFT during any of the games.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It makes sense for HIIT to include SSGs since the players would also improve technical and tactical elements and their decision-making processes, which are required for playing soccer ( Davids et al, 2013 ; Trecroci et al, 2020 ) Therefore, the next aim was to determine if participants would exceed the ANT and achieve PFT intensity during four-versus-four matches on a 25 m × 35 m pitch that reflect the game conditions required in the specific HIIT proposed. The parameter frequently used in coaching practice to determine the effort intensity during the game is HR ( Brandes et al, 2012 ; Aşçı, 2016 ; Konefał et al, 2023 ), which can be measured with precision and accuracy using available measurement technologies ( Beenham et al, 2017 ; Gómez-Carmona et al, 2020 ; Pop et al, 2022 ). In this study, soccer players achieved HR max values that exceeded the intensity found at the ANT five-fold during six 3-min matches, even though they did not reach such intensity at the PFT during any of the games.…”
Section: Discussionmentioning
confidence: 99%
“…External loads were determined using a global positioning system (GPS) with sampling at 10 Hz and triaxial accelerometer sampling at 100 Hz using the Vector S7 (Catapult Sports, Melbourne, Australia) ( Beenham et al, 2017 ). Data were collected after each session using Catapult Sports’ proprietary software (OpenField) ( Pop et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%